Plant-based dietary index on the Mediterranean and a vegan diet: a secondary analysis of a randomized, cross-over trial - Kahleova, Hana; Smith, Reagan; Fischer, Ilana; Brennan, Haley; Znayenko-Miller, Tatiana; Holubkov, Richard; Barnard, Neal D. (Frontiers in Nutrition, 2025)
ObjectiveThe plant-based diet index (PDI) has been proposed as a gauge of diet healthfulness. This study assessed the relationship between the PDI, and the “healthful” hPDI and “unhealthful” uPDI, and weight loss in the context of Mediterranean and vegan diets in overweight adults.MethodsIn a cross-over trial, 62 overweight adults followed a Mediterranean and a low-fat vegan diet for 16 weeks in random order, separated by a 4-week washout. Body weight was the primary outcome. In a secondary analysis, three-day dietary records were analyzed, PDI indices were calculated. Their correlation with changes in body weight was assessed, using Spearman correlations.ResultsCompared with no change on the Mediterranean diet, PDI significantly increased on the vegan diet; effect size: +7.6 (95% CI +4.1 to +11.0); p < 0.001. The hPDI score increased on both diets; effect size: +3.8 (95% CI −0.0 to +7.6); p = 0.05. The uPDI score decreased on the Mediterranean diet, while it increased on the vegan diet; effect size: +11.9 (95% CI +8.9 to +14.8); p < 0.001. In the first 16 weeks of the study, across both diets, changes in PDI and uPDI were negatively associated with changes in body weight, i.e., increases in PDI and uPDI were associated with weight loss: r = −0.32; p = 0.01; and r = −0.47; p < 0.001, respectively. These associations remained significant even after adjustment for changes in energy intake. No association was observed between changes in hPDI and changes in body weight.ConclusionThese findings suggest that, replacing animal products even with the “unhealthful” plant-based foods on a vegan diet was associated with weight loss.Clinical trial registrationClinicalTrials.gov, identifier NCT03698955.